The Effect of Implementing ESD in the PBL Model on Critical Thinking Ability in Environmental Pollution Material - Maulina, Dina; Hikmawati, Anisa; Marpaung, Rini Rita T (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2023)
Education for Sustainable Development (ESD) is an effort to realise the goals listed in the SDGs. ESD is an alternative approach to the field of education to prepare a generation that has an awareness of sustainable life. The purpose of this study is to analyze the effect of the application of the problem-based learning model on students' critical thinking skills on SDGs-oriented environmental pollution materials. The research method employed was a quasi-experimental with the control group pretest-posttest design. In determining the sample, the researchers employed purposive sampling techniques by considering the differences in academic achievement, differences between the two classes, and differences in the number of students. Therefore, class VII B with 27 students was chosen as the experimental class and class VII E with 25 students was chosen as the control class. The types of data used were quantitative. The pretest-posttest in the experimental class obtained an N-gain score of 0.58 in the medium criterion. The normality test in the experimental class obtained a score of Sig 0.48, which was lower than 0.05. Conversely, the control class obtained a score of Sig 0.20, which was lower than 0.05. The homogeneity result was Sig 0.12, which was lower than 0.05. The hypothesis testing using the independent-sample t-test, a Sig (2-tailed) value of 0.00 was obtained, and the results of the effect size test were 1.77 with the high criterion. Therefore, there was a significant effect of using the SDG-oriented PBL model towards critical thinking skills on the topic of environmental pollution.